I'm dirty! - McMullan, Kate.; McMullan, Jim, 1936- (New York : Joanna Cotler Books, 2006)
A busy backhoe loader describes all the items it hauls off a lot and all the fun it has getting dirty while doing so.
Accelerated Reader AR
Keywords: Backhoes -- Fiction; Cleanliness -- Fiction